A survey in wireless sensor network for explosives detection. (November 2018) - AL-Mousawi, Ali Jameel; K. AL-Hassani, Haider.
Abstract: Explosive detection techniques are one of the most important modern technologies for saving civilian lives from terrorist operations. Technological advances and the development of explosive detection have greatly reduced the proportion of terrorist operations around the world. One of the most modern technologies that assist in the detection of explosives is the use of wireless sensor network. In this paper, modern practical studies of the wireless sensor network in explosives detection field have been taken into consideration and statistics are being conducted on these studies. Explosive detection requires the use of special sensors and compatible to work with the wireless sensor network. This paper deals with three main axes in wireless sensor systems: first axes is the scalability of wireless sensors in explosives detection technology. Second axes of WSN explosives detection system is the communication and mobility of these networks and sensors. The latest axes discuss the data security of the wireless sensor network used in the process of detecting explosives and the potential dangers that the system can direct in terms of data security.